2015
DOI: 10.1016/j.neubiorev.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Negative affective states and cognitive impairments in nicotine dependence

Abstract: Smokers have substantial individual differences in quit success in response to current treatments for nicotine dependence. This observation may suggest that different underlying motivations for continued tobacco use across individuals and nicotine cessation may require different treatments in different individuals. Although most animal models of nicotine dependence emphasize the positive reinforcing effects of nicotine as the major motivational force behind nicotine use, smokers generally report that other con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 268 publications
(324 reference statements)
2
63
2
1
Order By: Relevance
“…Nicotine was infused through subcutaneous osmotic minipumps at concentrations of 14 and 40 mg/kg/day (Model 2004, ALZET, Palo Alto, CA). Doses were chosen based on previous reports of effects in mice (Stoker et al 2008; Portugal and Gould 2009; Hall et al 2015). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotine was infused through subcutaneous osmotic minipumps at concentrations of 14 and 40 mg/kg/day (Model 2004, ALZET, Palo Alto, CA). Doses were chosen based on previous reports of effects in mice (Stoker et al 2008; Portugal and Gould 2009; Hall et al 2015). …”
Section: Methodsmentioning
confidence: 99%
“…It is now commonly accepted that the difficulty of smoking cessation is, in part, due to the cognitive deficits associated with nicotine withdrawal (Hall et al 2015). Patients report difficulty concentrating and confusion with quantified nicotine withdrawal-induced impairments to working memory, attention, response inhibition, reward processing, and reaction time (Hughes 2007; McClernon et al 2015; van Enkhuizen and Young 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following chronic tobacco use, withdrawal from nicotine produces a milieu of withdrawal symptoms including physical signs, negative affective states and cognitive deficits (see Table 1; [4]). Growing evidence suggests that the physical signs of withdrawal are mechanistically distinct from negative affective states.…”
Section: Nicotine Reward and Withdrawalmentioning
confidence: 99%
“…Studies using IV and oral SA procedures have also shown that nicotine intake is higher in adolescent versus adult rats [23][24][25][26][27][28] and mice [29]. High doses of For a recent and comprehensive review of the physical and affective states produced by withdrawal in rodents and humans, the reader is referred to Hall et al [4] nicotine also produce aversive effects that are lower in adolescent versus adult rats [18,30]. With regard to withdrawal, clinical studies have revealed that young smokers exhibit milder symptoms of withdrawal during abstinence from smoking [31], and they are less responsive to cessation approaches that alleviate withdrawal [32][33][34].…”
Section: Tobacco Use In Vulnerable Populationsmentioning
confidence: 99%